Meningkatkan Kapasitas Pendampingan Siswa Disabilitas melalui Kewirausahaan Berbasis Teknologi - Nurcahya, Yulida Army; Utami, Martiana Riawati; Khotijah, Siti Afidatul; Arnandha, Yudhi; Agita, Sherindea Permata (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service aims to increase the capacity of parents of students with disabilities at SLB-B YPPALB Magelang City through digital-based entrepreneurship training. The program was initiated due to parents' lack of knowledge in mentoring children with disabilities and limited understanding of how to help them become independent. The method applied includes lectures, tutorials, and discussions that focus on digital parenting and entrepreneurship motivation. The results show that parents have gained new knowledge about digital parenting and have been motivated to assist their children in developing independent entrepreneurial activities. The program has successfully enhanced parents’ understanding of supporting their children’s skills in entrepreneurship and introduced them to the concept of halal product certification.